Meningkatkan Hasil Belajar PKN Menggunakan Model Pembelajaran Inkuiri Terbimbing Pada Kelas VII MTs Raudlatul Hasaniyah Tahun Ajaran 2023 - 2024 - Nasrul Ulum; Uswatun Hasanah; Didit Yulian Kasdriyanto (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Lack of educator skills in choosing learning models has a very real impact on the learning outcomes that students will achieve. Low student learning outcomes are due to lack of motivation and student activity to be directly involved in learning. So researchers are very interested in conducting research and taking action to overcome the problems that occur. At MTs Raudlatul Hasaniyah, Civics learning outcomes looked very low, so the researchers took the solution of implementing the Guided Inquiry learning model to improve students' learning outcomes and learning activities. The research subjects were 20 class VII students at MTs Raudlatul Hasaniyah. This research was carried out in the Classroom Action Research (CAR) model. The data collection process is through observation, interviews, documentation and learning outcomes tests. The data analysis process uses qualitative descriptive and quantitative descriptive. The results obtained showed an increase from cycle 1, the average learning outcome was 59 to 81.75 in cycle 2 and the average student learning activity in cycle 1 was 49.09 to 76.36 in cycle 2. This means that the use of the Guided Inquiry learning model is very significantly to improve student learning outcomes and learning activities.